A linear tetranuclear Cu(II) complex exhibiting both ferro and antiferromagnetic couplings: Synthesis, characterization and magneto-structural studies. (1st June 2019) - Anwar, Muhammad U.; Al-Harrasi, Ahmed; Pilkington, Melanie; Gavey, Emma L.; Rawson, Jeremy M.
Graphical abstract: A linear Cu4 complex containing a combination of square pyramidal and octahedrally coordinated Cu(II) ions is reported. The metal centres are linked via diazine and chloride bridges. Magnetic studies reveal the presence of strong antiferromagnetic interactions via the diazine bridge and moderate ferromagnetic interactions via the chloro bridges. Abstract: The pyrimidinyl hydrazone ligand OCNHNC(Me)(pm)2 (pm = 2-pyrimidinyl) (L3 H2 ) has two potentially protic H atoms and multiple donor atoms. The reaction ofL3 H2 with CuCl2 ·2H2 O yielded the tetranuclear complex [Cu4 (L3 H)2 Cl6 (CH3 OH)2 ] (1 ). Structural studies on1 reveal the molecule is located about a crystallographic inversion centre, affording two crystallographically independent Cu(II) centres with the two symmetry equivalent [Cu2 (L3 H)Cl3 CH3 OH] units connected via µ2 -Cl bridges to generate a linear tetranuclear copper complex. The ligand is singly deprotonated (L3 H − ) and twisted around the diazine NN′ bond, affording an N3 donor set for the Cu1 centre and an N2 O donor set for the Cu2 centre. The Cu1 ion is five coordinate with an [N3 ] donor set from theL3 H − ligand and the remaining two sites occupied by Cl − anions. The Cu2 ion is six coordinate with theL3 H − ligand offering a mer [N2 O] donor set, with the three remaining sites occupied by two Cl − anions and a MeOH molecule. Magnetic studies reveal the presence of strong antiferromagnetic interactions via the diazine bridge linking the Cu1 and Cu2 ions and moderate ferromagnetic interactions via the chloro bridges located about the inversion centre, connecting the Cu2 and Cu2i ions.